Le commerce de céramiques fines à ammaia, une ville du sud de la Lusitanie (50 - 550 Apr. J.-C.) - Quaresma, José Carlos da Costa, (Roman and late antique Mediterranean pottery ;, 2021)
This volume presents the entire assemblage of fine wares (terra sigillata, lamps and thin-walled wares) from Ammaia, a Roman and Late Antique town located in the hinterland of southern Lusitania (presently in Portuguese territory).